2019
DOI: 10.21767/1791-809x.1000633
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology of Acute Myocardial Infarction in Setif, Algeria: Finding from the Setif-AMI Registry

Abstract: Objectives and Introduction: According to the most recent global burden diseases study (2017), Algeria and the Middle East countries are classified as high mortality countries of acute coronary syndrome, with a 26% increase in period from 1990 to 2017. The objectives of this article are first to detail the methodology and design of the Setif-AMI registry, 4-year registration criteria for patients with STEMI (ST Elevation Myocardial Infarction) and NSTEMI (Non-ST Elevation Myocardial Infarction), to explore the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…NSTEMI accounted for 47.52% of cases (1317 patients). (16) This current study shows that the frequency of STEMI among males was 50% and 20.4% for females while NSTEMI among males was 16.6% and 13% among females.While Tunisia study in revealed that STEMI in males constituted 37.8% and 14.6% females while NSTEMI among males was 32.1% and 15.4% females . (16) .…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…NSTEMI accounted for 47.52% of cases (1317 patients). (16) This current study shows that the frequency of STEMI among males was 50% and 20.4% for females while NSTEMI among males was 16.6% and 13% among females.While Tunisia study in revealed that STEMI in males constituted 37.8% and 14.6% females while NSTEMI among males was 32.1% and 15.4% females . (16) .…”
Section: Discussionsupporting
confidence: 45%
“…(16) This current study shows that the frequency of STEMI among males was 50% and 20.4% for females while NSTEMI among males was 16.6% and 13% among females.While Tunisia study in revealed that STEMI in males constituted 37.8% and 14.6% females while NSTEMI among males was 32.1% and 15.4% females . (16) . These differences in the prevalence of acute MI(STEMI/NSTEMI) and frequency among males and females might be due to difference in the sample size and duration of study.…”
Section: Discussionsupporting
confidence: 45%
“…Patients with STEMI were significantly younger than the patients with NSTEMI, which might be explained by the higher rates of collaterals in older patients. TURKMI patients were similar in age compared with Iranian ( 21 ), Mexican ( 23 ), and Algerian ( 20 ) MI patients at the time of the index MI ( Fig. 5 ), whereas the average MI age was younger (56 years) in Saudi Arabian MI patients ( 19 ).…”
Section: Discussionmentioning
confidence: 85%